Factors predicting learning performance in flipped classroom: A survey study based on RCoI framework - Jimei Gao; Tan, Choon Keong (Spanish Ministry of Education, Culture and Sport, 2025)
While previous studies have focused on the factors affecting flipped learning performance, few have examined these factors through the lens of the Community of Inquiry framework. This study investigated how Teaching Presence, Social Presence, Cognitive Presence, and Emotional Presence, as defined by a revised Community of Inquiry framework, predict flipped learning performance. The analysis employed correlation analysis and two-step hierarchical multiple regression methods and was conducted in a flipped Fundamentals of Computer Application course (N=503) at a private polytechnic university in China. The results revealed that Teaching Presence, Social Presence, Cognitive Presence, and Emotional Presence were all significantly correlated with learning performance. However, only Teaching Presence, Cognitive Presence, and Emotional Presence were significant predictors of flipped learning performance, while Social Presence was not. The findings offer both theoretical insights and practical implications for improving instructional design and classroom organization in flipped learning environments.